Transurethral Resection (TURP) Versus Transurethral Incision (TUIP) of the Prostate for Small Sized Benign Prostatic Hyperplasia: A Prospective Randomized Study (TAJ: Journal of Teachers Association, 2009)
In a prospective, randomized study, 80 patients with lower urinary tract symptoms (LUTS) caused by small prostate gland (estimated weight 0.001) less in TUIP group than that of TURP.In conclusion, we recommend TUIP for the treatment of LUTS caused by small size obstructing benign prostatic hyperplasia.   doi: 10.3329/taj.v19i2.3149 TAJ 2006; 19(2): 50-56